Influence of Elevated Temperatures on the Compressive Strength of Concrete Made with Different Types of Aggregate - Seyam, Ahmed M.; Nemes, Rita (Periodica Polytechnica Civil Engineering, 2024)
Concrete, the backbone of modern infrastructure, exhibits varying mechanical behaviour that depends on its components, with aggregates playing a crucial role in its strength and durability. This study aimed to investigate the influence of elevated temperatures on the compressive strength of concrete made with different types of aggregate. A comprehensive evaluation of concrete mixes was conducted using quartz, crushed clay bricks, crushed andesite, expanded clay and expanded glass coarse aggregates. For each coarse aggregate type, concrete mixtures were made with the same amount of Portland cement, water-cement ratio, natural sand, and superplasticizer. The effective water-cement ratio and cement content were kept constant in each concrete mixture. The grading and maximum particle size were the same in all concrete mixtures. The results revealed that the type of aggregate has a significant impact on the compressive strength and thermal resistance of concrete, with andesite-containing concrete exhibiting the highest residual strength after heating up to 800 °C and clay brick-concrete displaying the highest strength under elevated temperatures up to 1000 °C. The study also found that the age of concrete affects its strength at elevated temperatures, as concrete in the early stages of hydration is more susceptible to thermal cracking than concrete that has had more time to cure. Generally, the compressive strength of normal-weight aggregates depends on the strength of the parent rock. But in the case of fire (elevated temperature), the cement paste matrix loses its strength, and the aggregates effects become more significant.